Concurrent Tuberculous Meningoencephalitis and Anti-NMDAR Encephalitis: A Case Report - Xiaoli, Chen; Qun, Wang; Jing, Li; Huan, Yang; Si, Chen (Frontiers in Neurology, 2022)
Background Cases of tuberculosis triggering the development of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis are absent. Case Presentation Herein, we report, for the first time, the case of a patient who developed anti-NMDAR encephalitis likely due to tuberculosis. The patient, a 33-year-old man, experienced weight loss during the previous 2 years, along with acute headache, fever, cognitive deficits, and right ophthalmoplegia. Based on these findings and on data from magnetic resonance imaging and cerebrospinal fluid antibody analysis, tuberculous meningoencephalitis combined with anti-NMDAR encephalitis was diagnosed. Marked clinical and brain imaging improvement were observed after antituberculosis and high-dose corticosteroid treatment initiation, which persisted during the 3 months of follow-up. Conclusions This case suggests that anti-NMDAR encephalitis may arise after tuberculosis infection. Therefore, clinicians must be aware of this possibility, especially when cognitive and new neurological symptoms suddenly occur.